Mastering operational risk : a practical guide to understanding operational risk and how to manage it - Blunden, Tony (Pearson, 2013)
A practical guide, from the basic techniques, through to advanced applications, showing you what operational risk is, and how you can manage it. Mastering Operational Risk provides a step-by-step guide from the basic elements of operational risk through to advanced applications of operational risk management. Focusing on practical applications, it givesyou the knowledgeneeded to understand what operational risk is and puts in place a workable way of managing it.